Response mechanisms of surrounding rock and tunnel structures of a karst tunnel under high operational water pressure - An Pengtao; Zhou Liangdong; Yang Shiwei; Zhang Jiabing; Fu Helin (Hydrogeology Journal, 2026)

Integrative metabolomic and genomic characterization of the high antimicrobial activity of Lacticaseibacillus paracasei and its potential for juice preservation - Fu Wei; Yanmei Sun; Yaping Mi; Chen Liang; Meichi Yue; Kehui Zhang; Rui Dong; Ziyi Zhang; Qiannan Yang; Songtao Guo; Shiwei Wang (Food Research International, 2026)

Rock-Breaking Analysis and Structural Optimization of Convex-Ribbed Ridged Nonplanar PDC Cutters and Application - Lian Chen; Chuan Hu; Yingxin Yang; Xiaoqiang Peng; Zhengwei Li; Shiwei Niu; Jiayuan Zhao; Zhiqiang Fu (Rock Mechanics and Rock Engineering, 2026)

Integrative transcriptomic and epigenomic analysis reveals the molecular mechanism of light-enhanced calcification in giant clams - Wenjie Yi; Fan Mao; Ke Wan; Shiwei Fu; Md. Abu Kawsar; Xiangcheng Yuan; Jun Li; Zhiming Xiang; Shu Xiao; Weihua Zhou; Ziniu Yu; Yang Zhang (Aquaculture, 2026)

Long-term enhanced nitrogen removal and power generation in high-salinity ammonium-rich wastewater treatment via heterotrophic nitrifying-aerobic denitrifying bacteria-functionalized biocathodes - Linfang Zhang; Yishen Xu; Qi Zhuang; Houxiang Feng; Guokai Fu; Yuhao Zhang; Shiwei Cao (Bioresource Technology, 2026)

NO2-promoted heterogeneous photochemical oxidation of SO2 to sulfates on brown carbon - Hongxing Yang; Wangjin Yang; Shiwei Lai; Fu Li; Shaojie Yang; Chong Han (Environmental Pollution, 2025)

Corrigendum to “Open pocket and tighten holes: Inhalable lung cancer-targeted nanocomposite for enhanced ferroptosis-apoptosis synergetic therapy” [Chem. Eng. J. 458 (2023) 141487] - Wenhua Wang; Wenhao Wang; Shiwei Jin; Fangqin Fu; Zhengwei Huang; Ying Huang; Chuanbin Wu; Xin Pan (Chemical Engineering Journal, 2025)

Optimizing N applications increases maize yield and reduces environmental costs in a 12-year wheat-maize system - Shuaijie Shen; Biao Feng; Datong Zhang; Jun Zou; Yuhao Yang; Robert M. Rees; Cairistiona F.E. Topp; Suya Hu; Bowen Qiao; Wenhai Huang; Hongbao Sun; Shiwei Zhou; et al. (Field Crops Research, 2025)

Unraveling the role of oxygen vacancies in enhancing the SO2-resistance of α-MnO2 towards elemental mercury removal - Qian Yu; Fei Lai; Shiwei Sheng; Yujia Wang; Bo Yuan; Dong Fu (Chemical Engineering Journal, 2025)

Projection of future drought impacts on millet yield in northern Shanxi of China using ensemble machine learning approach - Shiwei Zhou; Yangzhong Wu; Chu Wang; Huayu Lu; Zecheng Zhang; Zijin Liu; Yongdeng Lei; Fu Chen (Computers and Electronics in Agriculture, 2024)

Single-actuated and fully recyclable phase change materials enabled multiple thermochromism toward information storage and encryption - Shiwei Zhao; Anqian Yuan; Xingbao Chen; Yuan Lei; Xiaowei Fu; Jingxin Lei; Liang Jiang (Chemical Engineering Journal, 2024)

Soil health assessment under different soil and irrigation types in the agro-pastoral ecotone of northern China - Huayu Lu; Xiangyang Chen; Ke Ma; Shiwei Zhou; Jiali Yi; Yunjiao Qi; Jiale Hao; Fu Chen; Xinya Wen (CATENA, 2024)

Using association mapping and local interval haplotype association analysis to improve the cotton drought stress response - Wenju Gao; Qin Chen; Jincheng Fu; Hui Jiang; Fenglei Sun; Shiwei Geng; Yuxiang Wang; Jieyin Zhao; Yuting Xie; Man Zhou; Yanying Qu; Quanjia Chen (Plant Science, 2023)

Motor intent recognition of multi-feature fusion EEG signals by UMAP algorithm - Yushan Du; Jiaxin Sui; Shiwei Wang; Rongrong Fu; Chengcheng Jia (Medical & Biological Engineering & Computing, 2023)

Large‐scale exploration of nitrogen utilization efficiency in Asia region for rice crop: Variation patterns and determinants - Yuming Sun; Limin Gao; Xusheng Meng; Jian Huang; Junjie Guo; Xuan Zhou; Guohai Fu; Yang Xu; Leslie G. Firbank; Min Wang; Ning Ling; Xumeng Feng; et al. (Global Change Biology, 2023)
Improving rice nitrogen utilization efficiency (NUtE) is imperative to maximizing future food productivity while minimizing environmental threats, yet knowledge of its variation and the underlying regulatory factors is still lacking. Here, we integrated a dataset with 21,571 data compiled by available data from peer‐reviewed literature and a large‐scale field survey to address this knowledge gap. The overall results revealed great variations in rice NUtE, which were mainly associated with human activities, climate conditions, and rice variety. Specifically, N supply rate, temperature, and precipitation were the foremost determinants of rice NUtE, and NUtE responses to climatic change differed among rice varieties. Further prediction highlighted the improved rice NUtE with the increasing latitude or longitude. The indica and hybrid rice exhibited higher NUtE in low latitude regions compared to japonica and inbred rice, respectively. Collectively, our results evaluated the primary drivers of rice NUtE variations and predicted the geographic responses of NUtE in different varieties. Linking the global variations in rice NUtE with environmental factors and geographic adaptability provides valuable agronomic and ecological insights into the regulation of rice NUtE.

Open pocket and tighten holes: Inhalable lung cancer-targeted nanocomposite for enhanced ferroptosis-apoptosis synergetic therapy - Wenhua Wang; Wenhao Wang; Shiwei Jin; Fangqin Fu; Zhengwei Huang; Ying Huang; Chuanbin Wu; Xin Pan (Chemical Engineering Journal, 2023)

Construction of the dynamic model of SCI rehabilitation using bidirectional stimulation and its application in rehabilitating with BCI - Zhengzhe Cui; Juan Lin; Xiangxiang Fu; Shiwei Zhang; Peng Li; Xixi Wu; Xue Wang; Weidong Chen; Shiqiang Zhu; Yongqiang Li (Cognitive Neurodynamics, 2023)

Microbial functional communities and the antibiotic resistome profile in a high-selenium ecosystem - Yanmei Sun; Jia Guo; Fu Wei; Xiaohui Chen; Meng Li; Chao Li; Size Xia; Guangming Zhang; Wencai You; Xin Cong; Tian Yu; Shiwei Wang (Chemosphere, 2023)

Brain-Wide Shape Reconstruction of a Traced Neuron Using the Convex Image Segmentation Method - Shiwei Li; Tingwei Quan; Hang Zhou; Qing Huang; Tao Guan; Yijun Chen; Cheng Xu; Hongtao Kang; Anan Li; Ling Fu; Qingming Luo; Hui Gong; et al. (Neuroinformatics, 2020)

Identifying Weak Signals in Inhomogeneous Neuronal Images for Large-Scale Tracing of Sparsely Distributed Neurites - Shiwei Li; Tingwei Quan; Hang Zhou; FangFang Yin; Anan Li; Ling Fu; Qingming Luo; Hui Gong; Shaoqun Zeng (Neuroinformatics, 2019)

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

Hpyerglycemic effect of a mixture of sea cucumber and cordyceps sinensis in streptozotocin-induced diabetic rat - Shiwei Hu; Jingfeng Wang; Zhaojie Li; Jia Fu; Yuming Wang; Changhu Xue (Journal of Ocean University of China, 2014)